Payment perception in the emergency department: The mediating role of perceived quality of healthcare and patient satisfaction - Abidova, Alina (2024)
The aim of this research is to identify the main factors associated with patients’ payment perception and the effects of these factors on payment perception. Patients admitted between January and December 2016 at an emergency department of a public hospital in Lisbon, Portugal, were included in this study, with a representative sample size of 382 patients. A 5% margin of error and a 95% confidence interval were used, and all the data were collected between May and November 2017. To test the mediation models, stepwise multiple linear regression analysis was used. The effect of doctors on payment perception through satisfaction and through perceived quality of healthcare (PQHC) is explained by 3% and 4% of the variation, respectively, with statistically significant results (P < .01). Moreover, the effect of privacy and meeting expectations on payment perception through PQHC is explained by 4% and 4% of the variation, with statistically significant results (P < .01). Doctors play a crucial role in understanding the patients’ payment perception (with direct and indirect effects). Mediators, in turn, strengthen this effect, in which the contribution of PQHC is more significant than that of satisfaction.